Agricultural family schools in the "Pampa Gringa", historical traces between the particular and the universal - Southwell, Myriam (2020)
Agricultural Family Schools have been the way to concretize a model of pedagogy of alternation, an education modality that has been little investigated from a historical point of view. This article aims to present the emergence of alternating pedagogy in Europe, its influence in the South American territory, and to analyse in more detail its expansion in Argentina from the late 1960s. We are interested in dwelling on these alternative modes of conceiving and building schools not only because of their value as a contribution to agricultural education at the secondary level, but also as a contribution to research on specific historical experiences which constitute areas for inscription of school innovations, pedagogical debates, struggles and resistance (McLeod, 2014). Likewise, we are interested in analysing this alternative modality of schooling from the conceptual debate on the tension between the particular and the universal, which is expressed in this different way of conceiving teaching and learning and analysing the hegemony of the school format (Southwell, 2008). To do this, we carry out a historical analysis of the testimonies that recorded the emergence, debates and expansion of these institutions, as well as the educational concepts that were configured in the historical journey developed until today.
Keywords: Pedagogy of alternation; Agricultural family schools; Particularism; Universalism